Analysis of Bank Soundness Before and After the Pandemic: The RGEC Approach - Alif Misbachul Arifin (Journal of Economics Research and Social Sciences, 2022)
The Covid-19 pandemic has affected activities in the financial services industry, especially the banking sector, due to a slowdown in the real sector and the corporate sector, which has not yet been able to operate thoroughly. Therefore, amid a pandemic like this, it is increasingly necessary for banks to maintain and improve their level of soundness so that they can minimize possible risks and identify problems earlier. Concerning the soundness of the banks, banks are required to conduct periodic self-assessments and take corrective measures effectively by using an assessment of several factors, including risk profile, good corporate governance (GCG), earnings, and capital, abbreviated as RGEC. This study aims to determine whether there are statistical differences in banking health conditions before and after the Covid-19 pandemic. The case studies used in this study were 13 banking companies listed on the Kompas 100 Index. Using the t-test and Wilcoxon test, no statistical differences were found in the level of bank soundness before and after the pandemic for each RGEC indicator except the loan to deposit ratio (LDR), return on earnings (ROE), return on assets (ROA), and operating costs of operating income (BOPO). This finding shows the lower liquidity capacity of banks after the pandemic.